Cover Feature: Sub‐Ensemble Monitoring of DNA Strand Displacement Using Multiparameter Single‐Molecule FRET (ChemPhysChem 5/2018). Issue 5 (28th February 2018) - Baltierra‐Jasso, Laura E.; Morten, Michael J.; Magennis, Steven W.
Abstract : The Cover Feature illustrates the use of multiparameter single‐molecule fluorescence spectroscopy as a sensitive tool for monitoring strand displacement from DNA nanostructures. The large parameter space allows the simultaneous monitoring of multiple reactants and products, with the potential to study more complex reactions. More information can be found in the Communication by L. E. Baltierra‐Jasso et al. onpage 551 in Issue 5, 2018 (DOI:10.1002/cphc.201800012 ).